DEVELOPMENT OF AN EFFICIENT TRAP FOR LOBSTER FISHING - RAJAN, K. V MOHAN; MEENAKUMARI, B; NAIR, A.K KESAVAN (Fishery Technology, 2017)
A modified trap was developed for fishing spiny lobsters. Experimental fishing was conducted using this trap along with traditional trap (as control) to assess the comparative efficiency: Design details and comparative efficiency of the modified trap is reported in this paper. From the analysis of variance, the difference :in average catches between the modified trap and the control is found to be highly significant establishing the high efficiency of new trap.